Molecular phylogeny and morphological diversity of the Niviventer fulvescens species complex with emphasis on species from China. Issue 2 (13th May 2020) - Ge, Deyan; Feijó, Anderson; Abramov, Alexei V; Wen, Zhixin; Liu, Zhengjia; Cheng, Jilong; Xia, Lin; Lu, Liang; Yang, Qisen
Abstract: The Niviventer fulvescens species complex (NFSC), a group of abundant and taxonomically ambiguous rodent taxa, is distributed from Southeast Asia to south-eastern China. We combined molecular and morphological datasets to clarify the species composition and variation of the NFSC. Our phylogenetic analyses, using molecular data, recovered eight genetic lineages in the NFSC, including a novel, distinct lineage from Jilong, Tibet, China, which is described as a new species, N. fengi sp. nov. The species status of N. fengi is supported by a species delimitation analysis, and it is morphologically distinguished from other members of the NFSC by its greyish dorsal fur, soft hairs covering the whole body and a hairy tail. NFSC species bearing well-developed spines are found at lower elevations. A comprehensive taxonomic revision of the NFSC within China is provided, represented by five species: N . cremoriventer, N . fulvescens, N . huang, N. mekongis comb. nov. and N. fengi. A further study of this species complex, including samples from Southeast Asia, is needed.